Core Training for Superior Sports Preparation - Judge, L. W. (Journal of Coaching Education, 2008)
The core is at the center of most sports movements. What the core musculature is, how it is evaluated, how it is trained, and how it is applied to functional performance can sometimes be confusing to coaches. The benefits of a sound, research-based core training program is essential to all sport; therefore it must be included in coach`s education. The core musculature is separated into two systems: local (stabilization) and global (movement). Exercises can be separated into three categories: core-stability, core-strength, and functional exercises. A multi-faceted approach that addresses the three planes of movement combining medicine-ball work, body-weight circuits, controlled movements, abdominal exercises, dumbbell complexes, and Olympic lifts can provide physiological and biomechanical advantages that enhance preparation for most every sport.